Clinical efficacy of vitrectomy when expressed destructive changes in the vitreous - A. V. Malyshev; V. N. Trubilin; V. D. Semykin (Oftalʹmologiâ)
Purpose: Conducting complex (clinical, hemodynamic, subjective) evaluate the effectiveness of vitrectomy in patients with expressed destructive changes in the vitreous (CT).Patients and methods. We observed 74 patients (86 eyes, mean age 63.4 years) with severe destructive changes CT manifested almost constant presence of «flying flies» in front of his eyes. Subtotal vitrectomy was performed by standard methods using instruments 25-30G with intraoperative use of a standard balanced salt solution (Balansed Salt Solution, BSS), further enriched with the introduction of an antioxidant (glutathione) in all patients in the main group.Results. Vitrectomy in patients with acute ST destructive changesassociated with significantly positive parametres of microcirculation (by 24,7 % –30,7 %, p <0,05) and subjective status (at 12,7 %, p <0,05), the progress after the surgery performance was not significantly different from that of the control group. There was a trend (p> 0,05) of increasing the maximum correctable visual acuity and the degree of lens opacity after surgery. The results of the the postoperative survey have shown that 92 % of patients were completely satisfied with the outcomes of operations (6 % — not satisfied, 2 % — had difficulties with answer). Subjectively, significant improvement in vision after surgery indicated in 62 % patients, eyesight was better — 26 %, unchanged — 10 %; blurred vision — 2 %. Our results regarding the dynamics of microcirculation suggest that surgical removal of the CT in expressed destructive changes lead to the normalization of the eyeball microvasculare perfusion. It is accompanied with the restoration of the natural balance between the arteriolar influx and venular outflow, as well as between the active and passive components of the regulatory microhemodynamics. These changes are responsible for the improvement of metabolic processes in the tissues of the eyeball, contributing to maintain a constant temperature and transparency of the CT, which generally provides the necessary prevention of postoperative complications in the retina.